Physical Characteristics of Tetrahydroxy and Acylated Derivatives of Jojoba Liquid Wax in Lubricant Applications - Rogers E. Harry-O’kuru; Girma Biresaw; Sherald Gordon; Jingyuan Xu (Journal of Analytical Methods in Chemistry)
Jojoba liquid wax is a mixture of esters of long-chain fatty acids and fatty alcohols mainly C38:2–C46:2. The oil exhibits excellent emolliency on the skin and, therefore, is a component in many personal care cosmetic formulations. The virgin oil is a component of the seed of the jojoba (Simmondsia chinensis) plant which occurs naturally in the Sonora Desert in the United States and northwestern Mexico as well as in the northeastern Sahara desert. The seed contains 50–60% oil by dry weight. The plant has been introduced into Australia, Argentina, and Israel for commercial production of the jojoba oil. As a natural lubricant, we are seeking to explore its potential as a renewable industrial lubricant additive. Thus, we have chemically modified the carbon-carbon double bonds in the oil structure in order to improve its already good resistance to air oxidation so as to enhance its utility as well as its shelf life in nonpersonal care applications. To achieve this goal, we have hydroxylated its –C=C– bonds. Acylation of the resulting hydroxyl moieties has generated short-chain vicinal acyl substituents on the oil which keep the wax liquid, improving its cold flow properties and also protecting it from auto-oxidation and rancidity.